Emergence of risk-based inspection and maintenance as an alternative maintenance approach for oil and gas facilities / Dabo Baba Hammada and Nasir Shafiq - Hammada, Dabo Baba; Shafiq, Nasir (2012)
An oil and gas plant is a complex system comprising various types of processing equipment consisting of mechanical, electrical, chemical and civil systems working under extreme conditions. The systems suffer increased wear with usage and age and are subject to random failures that are linked to the deterioration of these assets. A single or peculiar maintenance strategy may not serve the maintenance needs of this complex system. Hence, various maintenance approaches have to be tested and adopted for a particular cluster of systems or sub-systems. The general objective of the maintenance process is to make use of the knowledge of failures and accidents to achieve safety with the lowest possible cost. Bearing this philosophy in mind, Riskbased inspection has emerged as an alternative approach to time-based planned maintenance, condition-based proactive maintenance, and prediction-based preventive maintenance. These popular and historically long approaches were found to be practically unfit to contemporary competitive markets due to the tendencies of under or over inspection which may consequently lead to under of over allocation of maintenance resources on the one hand and under scoring of other social impacts of the plants and its system on the other hand. Therefore, this paper intends to review the philosophy, concept and types of Risk-based maintenance and its anticipated promises to civil structures in oil and gas facilities